Mexico - PROGRESA: breaking the cycle of poverty - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
For many of the world’s poor, public safety-net programs are the only hope for a life free from chronic poverty and undernutrition. But the proper combination of incentives and support can be difficult to achieve. The International Food Policy Research Institute’s in-depth evaluation of Mexico’s PROGRESA (Programa de Educación, Salud y Alimentación) indicates that antipoverty programs that combine education, health, and nutrition interventions in one package can be quite successful in improving the capacity of families to pull themselves out of the poverty that often ensnares generations. In collaboration with the Mexican government, IFPRI rigorously reviewed PROGRESA’s impact on education, nutrition, health and rural poverty, as well as the program's overall operation. The evaluation was based on repeated surveys of individuals from 24,000 households in 506 localities in randomly assigned PROGRESA and non-PROGRESA areas. Formal surveys, structured and semi-structured interviews, focus groups, and workshops were held in seven states where the program was first implemented on a pilot basis. The research asked a series of questions about PROGRESA’s effectiveness. This brief summarizes the research results.